Simulation and experimental verification of fatigue strength evaluation of journal bearing bush. (January 2020) - Dong, Qin; Yin, Zhongwei; Li, Hulin; Gao, Gengyuan; Zhong, Ning; Chen, Yonghong
Highlights: The fatigue strength of tin-base Babbitt bushes was simulated with FSI technique. The stress life decreased rapidly with the increase of specific pressure. The bearing fatigue tests were conducted on a sapphire fatigue testing machine. The simulation method can correctly predict the bearing fatigue strength. Abstract: The fatigue strength of journal bearing exampled with tin-based Babbitt bushes was calculated with fluid-structure interaction technique. The oil film pressure obtained by considering the cavitation in fluid simulation was loaded on the inner surface of bearing alloy as a boundary condition of fatigue analysis. The tests for the S-N curve of tin-based alloy were carried out in the hydraulic servo dynamic fatigue testing machine. To verify the simulation results, the bearing fatigue tests were conducted on the sapphire bearing bush fatigue testing machine with the same geometry, materials and boundary conditions as in the simulation. Results from simulation and experiment are quite consistent with each other.